Analisis Efek Ergogenik Kafein Terhadap Performa Atlet - Arimbi; Poppy Elisano Arfanda; Andi Ainun Zulkiah Surur; Ulfah Widyastuti Arsal; Andi Sri Dewi Anggraeni (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Caffeine is an ergogenic substance often used in sports to improve physical performance, particularly in cardiorespiratory endurance. This study aims to analyze the ergogenic effects of caffeine on athlete performance as measured by VO₂max capacity. The study used an observational design with a prospective study approach on 25 athletes. Data collection techniques were carried out through direct measurements of the research subjects. Data on athlete characteristics were collected by recording basic identity and initial physical condition, while VO₂max data were obtained through fitness tests using standard measurement procedures before and after caffeine administration. The intervention in the form of caffeine administration was carried out before physical activity according to a predetermined dose, then the athletes underwent VO₂max measurements after treatment. Data analysis used the Shapiro-Wilk normality test and paired t-test. The results showed that the average VO₂max increased from 41.02 ± 5.89 ml/kg/min to 44.85 ± 5.96 ml/kg/min with a significance value of p < 0.001. These findings demonstrate a significant effect of caffeine administration on improving athletes' cardiorespiratory endurance. Physiologically, caffeine works through adenosine receptor antagonism, increased fatty acid mobilization, and central nervous system stimulation, which contribute to delayed fatigue. Recent literature also supports that moderate caffeine consumption (3–6 mg/kgBW) effectively improves endurance performance. The conclusion of this study confirms that caffeine has a significant ergogenic effect in improving athlete performance, particularly on cardiorespiratory endurance components